2009
DOI: 10.1063/1.3212728
|View full text |Cite
|
Sign up to set email alerts
|

Excellent field emission from semialigned carbon nanofibers grown on cylindrical copper surface

Abstract: We report the field emission from carbon nanofibers (CNFs) grown directly on cylindrical copper by a simple pyrolysis technique. The turn-on field is 0.17 V/μm and the emission current density is 0.9 mA/cm2 at 0.35 V/μm. The emission current is stable at a field of 0.35 V/μm and 6.5×10−6 Torr. The excellent field emission behavior is attributed to the sp2 phase in CNFs and the stable emission is due to the direct growth. The direct growth on cylindrical cathode is advantageous for field emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The nanostructure growth over cylindrical surfaces has the advantage of getting higher FE currents as compared to the flat substrate. 35 A fundamental difficulty of nanostructure growth over a large area substrate may easily be overcome by extending this process by increasing the reactants in a proportionate amount. A typical digital image of nanospikes grown on a glass substrate having dimensions 6.5 cm  5 cm is shown here (see supporting information † Fig.…”
Section: X-ray Photoelectron Spectroscopic Investigationmentioning
confidence: 99%
“…The nanostructure growth over cylindrical surfaces has the advantage of getting higher FE currents as compared to the flat substrate. 35 A fundamental difficulty of nanostructure growth over a large area substrate may easily be overcome by extending this process by increasing the reactants in a proportionate amount. A typical digital image of nanospikes grown on a glass substrate having dimensions 6.5 cm  5 cm is shown here (see supporting information † Fig.…”
Section: X-ray Photoelectron Spectroscopic Investigationmentioning
confidence: 99%
“…As demonstrated previously, growing CNTs on metal substrates or on alloys containing one of the common catalyst metals can result in CNT films of high footprint density, which is electrically advantageous. For instance, Talapatra et al estimated an average total contact resistance of aligned CNTs on Inconel to be about 500 Ω, whereas measurements carried out on similar structures by Halonen et al showed the contact resistance is as low as ∼10 Ω (for a pattern footprint area of ∼0.4 cm 2 ). Although relatively low turn-on fields are observed for such devices, the maximum emission current densities reported were typically not higher than 10 mA/cm 2 . For CNTs to be used in field emission devices, it is not only essential to develop techniques to grow CNTs on conducting substrates but also to get good current density besides reducing the turn on and threshold voltages.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the good bonding and excellent conductivity by interface-controlled growth of CNTs directly on Cu current collectors, Li ion battery using the novel directly grown binder-free CNTs structure as anode showed very high specific capacity, almost three times as that of graphite, excellent rate capability even at a charging/discharging rate of 3 C, and no capacity degradation up to 50cycles (Lahiri, ea al., 2010). The CNT-based field emitters, prepared on metallic substrates by direct thermal chemical vapor deposition, exhibited a very low turn-on field, high emission current, long time stability and good resistance to degradation in high-field, long-time exposure (Mauger, et al, 2004& Sung, et al, 2008& Mahanandia, et al, 2009& Yi & Yang, 2010than straight CNTs . Several studies have revealed that CNTs have unusually high thermal conductivity in their axial direction (Berber, et al, 2000& Kim, et al, 2010.…”
Section: Applications Of Cnts Directly Grown On Bulk Metal Substratementioning
confidence: 99%